Impact of O' Level examination localization on assessment standards and credibility: a study of five high schools in the Kwekwe district of Zimbabwe. - Mangwaya, Ezron; Ndlovu, Emily (International Journal of Social Sciences and the Arts, 2016)
Localising examinations has been one of the key preoccupations of countries that did not have examination boards of their own. Zimbabwe, a country that has been using Cambridge overseas examinations for many years decided to localize examinations by creating a local examination hard well as setting and marking examination papers locally. This has had far reaching effects on assessment standards and examination credibility. This paper explores, through descriptive research, the impact of localizing O' level examinations on stakeholders' perceptions on assessment and credibility.